A utilização de recursos computacionais para o ensino da matemática financeira no ensino médio - COSTA, Neilton Vieira da (2015)
The objective of this paper is to nd strategies that can attract the attention of students in search of new knowledge, contributing to become critical citizens face the exploiter world in which we live. The subject of nancial mathematics was chosen thinking about two situations: rstly, because today we are surrounded by commercial transactions where people seek only pro t in the exploration of other, and secondly because we realize that this content is super cially studied in schools by placing the students only to memorize and to apply the formulas, without making a parallel with the nancial situations around them, thus, becoming anuseless and forgotten content for decision-making in future nancial transactions, to which each of these students will be submitted. Nowadays young people live amid so many technologies, and we believe that this is one of the reasons for which our students of basic education are not the least bit concerned about the proposed contents in schools. Facing that, we will explore each work situation, using free softwares like GeoGebra, WxMaxima and Microsoft Excel spreadsheets indicating resources for students to feel more attracted towards learning and for them to be able to use these technologies to analyze, to criticize and to simulate the nancial situations that surrounds them, both in the classroom and day-to-day.